Intestinal UDP-glucuronosyltransferase as a potential target for the treatment and prevention of lymphatic filariasis. - Alexander F Flynn; M Gordon Joyce; Rebekah T Taylor; Sasisekhar Bennuru; Alyssa R Lindrose; Spencer L Sterling; C Paul Morris; Thomas B Nutman; Edward Mitre (PLoS Neglected Tropical Diseases, 2019)
Lymphatic filariasis (LF), a morbid disease caused by the tissue-invasive nematodes Wuchereria bancrofti, Brugia malayi, and Brugia timori, affects millions of people worldwide. Global eradication efforts have significantly reduced worldwide prevalence, but complete elimination has been hampered by limitations of current anti-filarial drugs and the lack of a vaccine. The goal of this study was to evaluate B. malayi intestinal UDP-glucuronosyltransferase (Bm-UGT) as a potential therapeutic target. To evaluate whether Bm-UGT is essential for adult filarial worms, we inhibited its expression using siRNA. This resulted in a 75% knockdown of Bm-ugt mRNA for 6 days and almost complete suppression of detectable Bm-UGT by immunoblot. Reduction in Bm-UGT expression resulted in decreased worm motility for 6 days, 70% reduction in microfilaria release from adult worms, and significant reduction in adult worm metabolism as detected by MTT assays. Because prior allergic-sensitization to a filarial antigen would be a contraindication for its use as a vaccine candidate, we tested plasma from infected and endemic normal populations for Bm-UGT-specific IgE using a luciferase immunoprecipitation assay. All samples (n = 35) tested negative. We then tested two commercially available medicines known to be broad inhibitors of UGTs, sulfinpyrazone and probenecid, for in vitro activity against B. malayi. There were marked macrofilaricidal effects at concentrations achievable in humans and very little effect on microfilariae. In addition, we observed that probenecid and sulfinpyrazone exhibit a synergistic macrofilaricidal effect when used in combination with albendazole. The results of this study demonstrate that Bm-UGT is an essential protein for adult worm survival. Lack of prior IgE sensitization in infected and endemic populations suggest it may be a feasible vaccine candidate. The finding that sulfinpyrazone and probenecid have in vitro effects against adult B. malayi worms suggests that these medications have promise as potential macrofilaricides in humans.